Pemanfaatan Youtube sebagai Media Pemasaran Digital Produk Sarung Tenun UMKM Desa Wirun, Sukoharjo: Youtube as Digital Marketing Medium for Promoting the Product of Woven Sarong of MSME in Wirun, Sukoharjo - Wedhowerti, Wedhowerti; Astuti, Epata Puji; Iskarna, Tatang; Aji, Gabriel Fajar Sasmita; Widyastuti, Dewi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
MSME in Wirun, Mojolaban, Sukoharjo produces high-quality products of woven sarong. However, this product marketing has not reached a wider scope. This problem is mainly due to the unavailability of a digital marketing system. Departing from this fact, the English Letters Department of Universitas Sanata Dharma designed community service activities to be conducted in Wirun. This community service program was designed to introduce a bilingual digital marketing system as well as to work hand in hand designing and creating a bilingual YouTube channel as a medium for promotion and marketing. A series of activities began in March and ended in July 2024. The community service program was well executed. Workshop on digital marketing was fully delivered and the bilingual YouTube channel of “Sarung Tenun Desa Wirun” was successfully created.